Answer:
![X=B^(-1)A^(-1)BA+A](https://img.qammunity.org/2020/formulas/mathematics/high-school/eok41q9nm6h54q0cqmllmc6ozljzbjdpyd.png)
Explanation:
We are given that a matrix equation
![ABXA^(-1)B^(-1)=I+A](https://img.qammunity.org/2020/formulas/mathematics/high-school/22jvch20py644l2f1n8bgfjndoxaydvpc4.png)
We have to solve the given matrix equation for X.
Suppose all matrix are invertible.
Left multiply by
on both sides then ,we get
![B^(-1)A^(-1)ABXA^(-1)B^(-1)=B^(-1)A^(-1)(I+A)](https://img.qammunity.org/2020/formulas/mathematics/high-school/s8hxigjf4lmwkjygrspv0efhz2ooxkvbe9.png)
![B^(-1)BXA^(-1)B^(-1)=B^(-1)A^(-1)+B^(-1)A^(-1)A](https://img.qammunity.org/2020/formulas/mathematics/high-school/rmmihai6ux3t02opkc9rrnsmy9gxm2b9uz.png)
When A is invertible.
(
![B^(-1)B=BB^(-1)=I)](https://img.qammunity.org/2020/formulas/mathematics/high-school/1fylmzuuvxwjecvnznc8j4onovi2hvr4th.png)
Right multiply by BA on both sides then we get
![XA^(-1)B^(-1)BA=B^(-1)A^(-1)BA+B^(-1)BA](https://img.qammunity.org/2020/formulas/mathematics/high-school/75me3uxv51s8ehp17pc88x724zx1cxfps3.png)
![XA^(-1)A=B^(-1)A^(-1)BA+A](https://img.qammunity.org/2020/formulas/mathematics/high-school/l6tapw4jpxp5kkeo7d3mvr9zjn1z5d949o.png)
![XI=B^(-1)A^(-1)BA+A](https://img.qammunity.org/2020/formulas/mathematics/high-school/lsnqu1v68hvv0lorfgyxgfqwk7ux6xndss.png)
(XI=X)